How to use holographic tools to teach area and volume concepts - Orcos, Lara (Nova Science Publishers, Inc., 2022)
This chapter includes a methodological proposal based on the design of a material to be projected through a pyramidal holographic prism for the study of the concepts of areas and volumes of geometric bodies in the stage of Secondary Education. First of all, it has been carried out a bibliographic review about the difficulties involved in geometry learning process in the stage of Secondary Education, as well as on the foundation of the holography technique as a means of teaching and its involvement in geometrical content. Then, it is explined the design of a methodological proposal model based on a material to be projected on a tablet or mobile phone to form a hologram. For the creation of the figures and the videos, we have used GeoGebra® and Camtasia® respectively. © 2020 Nova Science Publishers, Inc.
Es un capítulo del libro: L. Orcos (2020), "Didactics of Mathematics: New Trends and Experiences": How to use holographic tools to teach area and volume concepts.
Keywords: areas and volumes of geometric bodies; Camtasia®; GeoGebra®; hologram; pyramid prisms; secondary education; tablet; Scopus(2)